Design and development of smokeless stove for a sustainable growth - Nayak, Ramesh Chandra; Roul, Manmatha K.; Roul, Prateek Debadarsi (Archives of Thermodynamics, 2022)
Air pollution has a serious impact on the health of human beings and is a major cause of death worldwide every year. Out of the many sources of air pollution, the smoke generated from household combustion devices is very dangerous due to the incomplete combustion of fuel. Women from rural areas suffer a lot due to this harmful smoke. Diseases like cancer, throat, and lung infection occur in adults and children due to inhalation of this smoke. The traditional chulha used by rural women is operated by using cow dung, straw, and wood, and the air is blown manually by using small metallic pipes. This paper presents the design and development of an innovative stove to maximize flame temperature and minimize air pollution to overcome the health-related issues of rural women. A smokeless stove is presented, in which wood, straw, and cow dung are taken as primary fuel, and superheated steam as a secondary oxidizer for its operation. In this stove, a forced draft is created by the provision of a small fan, which is operated by solar power thus eliminating the need of creating a forced draft manually by the cook which makes this innovative stove superior to the traditional chulha. Owing to the provision of superheated steam, the flame temperature as well as the burning efficiency increases. The cooking time is reduced due to higher flame temperature as compared to the liquefied petroleum gas stove. The main objective of this work is to minimize air pollution and provide a smoke-free environment to the people using such devices as this innovative stove offers complete combustion of fuel. The flame temperature of the designed stove ranges from 595˚C to 700˚C and its thermal efficiency is 10–17% higher than that of the traditional chulha. The design of this stove is unique, and its maintenance cost is also much less.
Keywords: combustion; efficiency; calorific value; air pollution; stove; fuel; superheater